Instructinonal Leadership Though Principal Supervision a Qualitative Study on Teacher Competence in Special Junior High Schools - Aini, Nur; Yasman Purnama, Boby (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
This study aims to examine how principal supervision is implemented in an effort to improve teacher competency in Special Needs Junior High Schools, as well as to identify supporting factors, inhibiting factors, and steps taken to overcome various supervision obstacles. The study used a descriptive qualitative approach involving the principal and six teachers as research subjects. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. Data validity was strengthened by triangulation techniques. The results showed that principal supervision was implemented in a planned and continuous manner through learning observations, individual supervision, and discussion forums with teachers. The implementation of this supervision contributed positively to improving teacher competency, particularly pedagogical, professional, social, and personality competencies in handling students with special needs. Supporting factors for supervision include the principal's commitment, teacher cooperation, and a conducive school climate, while obstacles faced were limited time, administrative burden, and learning facilities. To overcome these obstacles, the principal provided ongoing coaching and mentoring.